Trapnell's Upper Valley soils of Zambia: the production of an integrated understanding of geomorphology, pedology, ecology, and land use - N. L. Namwanyi; M. J. Hutton; I. Mukumbuta; L. M. Chabala; C. Chongo; S. Sichinga; R. M. Lark (SOIL)
The Ecological Survey of Northern Rhodesia (now Zambia), undertaken in the 1930s under the leadership of Colin G. Trapnell, was a seminal exercise to relate soil, vegetation, and agricultural practices through intensive field observation. In this article, we examine early activities of the survey in the Upper Valley region around the Kafue Flats and the neighbouring plateau, where Trapnell recognized how geomorphological processes of normal erosion gave rise to distinctive soils with associated vegetation communities and considerable potential for crop production. We consider how Trapnell's approach to fieldwork gave him a particular insight into how soil conditions constrained agriculture in the Zambian environment; the adaptive value of traditional practices; and how these were developed as communities moved and responded to social, economic, and environmental change. We argue that Trapnell's work was innovative and that distinctions must be drawn between his understanding and what has been called the ecological theory of development. Close attention to Trapnell's experience could inform modern efforts to understand indigenous knowledge of African soils and their agricultural potential.